Mobile Big Data A Roadmap from Models to Technologies - Skourletopoulos, Georgios; Mastorakis, George; Mavromoustakis, Constandinos X.; Dobre, Ciprian; Pallis, Evangelos (Lecture Notes on Data Engineering and Communications Technologies,, 2018)
This book reports on the latest advances in mobile technologies for collecting, storing and processing mobile big data in connection with wireless communications. It presents novel approaches and applications in which mobile big data is being applied from an engineering standpoint and addresses future theoretical and practical challenges related to the big data field from a mobility perspective. Further, it provides an overview of new methodologies designed to take mobile big data to the Cloud, enable the processing of real-time streaming events on-the-move and enhance the integration of resource availability through the 'Anywhere, Anything, Anytime' paradigm. By providing both academia and industry researchers and professionals with a timely snapshot of emerging mobile big data-centric systems and highlighting related pitfalls, as well as potential solutions, the book fills an important gap in the literature and fosters the further development in the area of mobile technologies for exploiting mobile big data.